Institutional Repository as a Knowledge Management Tool for the Enhancement of Library Visibility in the 21st Century: A Case of Midlands State University - Nyakurerwa, Austin Tonderai (IGI Global, 2022)
The chapter focused on the institutional repository as a knowledge management tool that enhances the visibility of libraries in the 21st century. The researcher mainly relied on content analysis to gather research data. The researcher took a swipe on the uptake of institutional repositories the world over and an analysis of how an institutional repository could be used as a knowledge management tool was done. The researcher also conducted a situational analysis of the MSU institutional repository and assessed the impact of the digital repository on the visibility of the library. The author used the Webometrics Ranking of Universities in Zimbabwe to assess how universities are ranked in Zimbabwe.